The Sadism of Jame Gumb in Thomas Harris’ Novel The Silence of The Lambs - Anggraini, Nina Nova (Journal of Language and Literature, 2015)
The backgrounds in this research for analyze is what are the causes main character perform in sadism. The aims of the study in this research, are to describe factors trigger Jame Gumb in performing sadism and to describe how Jame Gumb triggers sadism. The data in this research is taken from a novel. It is in the form of utterances and clauses reflecting the sadism of Jame Gumb. In analyzing the sadism that appear in the novel, the writer used descriptive qualitative method. The results of this study shown that Jame Gumb performed sadism because the background of life, he has a bad childhood, his mother is an alcoholic prostitute and his mother never gives attention, love and caring to him and he has killed and flayed at least eleven women, one of them is the first victim Klaus, who scalped and inserted pupa in her throat.Keywords: Jame Gumb, Sadism, Psychological Approach, Personality Disorder, The Silence of the Lambs.